Effects of Seasons and Zonation on Biochemical Contents of Two Seagrass Species along Dar es Salaam Coast, Tanzania - Mbaga, Wamwi M.; Mvungi, Esther F. (Tanzania Journal of Science, 2021)
Accumulation and allocation of biochemicals in plants are affected by various factors. The influence of seasons and vertical zonation on biochemical contents of seagrasses Cymodocea rotundata and Thalassia hemprichii from Mjimwema seagrass meadow along the coast of Dar es Salaam were assessed. Samples were collected in 2016 during wet/rainy (April–May) and dry (June–July) seasons. Concentrations of crude protein, soluble carbohydrates, phosphorus, lipid, and proline were determined using standard methods. Significant higher levels of phosphorus, lipid, protein and proline were observed during the dry season than in wet season (p < 0.05). Likewise, seagrass population occurring at the shore zone expressed higher levels of biochemical contents than those found at the subtidal zones. The highest concentration of protein was recorded in Thalassia hemprichii (5.8 mg/g dw)), while those of lipid and carbohydrates (27.1 and 53.1 mg/g dw, respectively) were recorded in Cymodocea rotundata. The two species studied did not vary significantly in their biochemical concentrations in both seasons. Generally it was observed that the concentrations of studied biochemicals were up-regulated during the dry season and varied depending on the locations where the seagrass grow. Thus, both season and zonation played roles in biochemical accumulation in the seagrasses understudy, however not interactively.